2012
DOI: 10.1159/000341934
|View full text |Cite
|
Sign up to set email alerts
|

Role of Supplementary <smlcap>L</smlcap>-Carnitine in Exercise and Exercise Recovery

Abstract: L-Carnitine is a conditionally essential nutrient and plays an important role in mitochondrial β-oxidation. As a dietary supplement for athletes, L-carnitine has been investigated for its potential to enhance β-oxidation during exercise ultimately to improve performance. While some studies have shown a positive impact on VO(2 max) and other performance measures, other studies have found contradictory results. As such, investigations to a different mechanism by which L-carnitine supplementation could impact exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…In accordance with CARN role in skeletal muscle, a large amount of research was directed towards investigating the effects of CARN supplementation on exercise performance [ 9 ], particularly in ameliorating and accelerating recovery from exercise-induced muscle injury [ 7 ]. It has been found that supplemental CARN is effective in attenuating signs of tissue damage induced by lengthening or intense contractions also in sarcopenic muscle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with CARN role in skeletal muscle, a large amount of research was directed towards investigating the effects of CARN supplementation on exercise performance [ 9 ], particularly in ameliorating and accelerating recovery from exercise-induced muscle injury [ 7 ]. It has been found that supplemental CARN is effective in attenuating signs of tissue damage induced by lengthening or intense contractions also in sarcopenic muscle [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, thus far, the body weight-reducing effect of L-carnitine supplementation has not been proven clinically [2]. A similar situation is characteristic of the use of L-carnitine for improved physical activity: L-carnitine is not considered a doping agent, but it has been shown to positively impact the recovery process after exercise [3]. In recent years, the first concerns regarding L-carnitine intake and cardiovascular health risks were published.…”
mentioning
confidence: 99%
“…Najbardziej znaną funkcją L-karnityny jest przyspieszanie procesu oksydacji lipidów w mitochondriach, co wpływa na redukcję tkanki tłuszczowej. Dzięki tej funkcji opóźnione zostaje również zmęczenie mięśni, w wyniku wolniejszego zużycia glikogenu, co pozwala na przeprowadzanie dłuższych i intensywniejszych treningów [27]. Sung i in.…”
Section: L-karnitynaunclassified